2004
DOI: 10.1016/j.jvs.2004.02.035
|View full text |Cite
|
Sign up to set email alerts
|

Effect of ethnicity on access and device complications during endovascular aneurysm repair

Abstract: Our data indicate that individuals of Asian ancestry are far more likely to experience adverse access-related and device-related complications after aortoiliac stent grafting than are non-Asians. We found that this association is at least partly attributable to the smaller and more tortuous iliac arteries in persons of Asian ancestry.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
38
1

Year Published

2008
2008
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 48 publications
(42 citation statements)
references
References 9 publications
(12 reference statements)
3
38
1
Order By: Relevance
“…23, 24 However, even though aortic dissection seems to occur more frequently in Asian countries, most of the literature regarding the anatomy of aortic dissection 19,20,25-28 and the ascending aorta/aortic arch 29-33 comes from Caucasian countries, with only a few exceptions. 18,34, 35 In this study, we performed a retrospective analysis of 131 Japanese TAAD patients.…”
Section: Discussionmentioning
confidence: 99%
“…23, 24 However, even though aortic dissection seems to occur more frequently in Asian countries, most of the literature regarding the anatomy of aortic dissection 19,20,25-28 and the ascending aorta/aortic arch 29-33 comes from Caucasian countries, with only a few exceptions. 18,34, 35 In this study, we performed a retrospective analysis of 131 Japanese TAAD patients.…”
Section: Discussionmentioning
confidence: 99%
“…22 Other studies have shown that the Asian population (men and women), who tend to be of smaller stature, are disadvantaged when being considered for endovascular aneurysm repair (EVAR), as the presence of smaller vessels is not conducive to easy deployment or long-term durability of the grafts. 23,24 Abdominal aortic aneurysms are four to six times more common in men than in women. 25 In addition, aneurysms develop in women approximately a decade later than in men.…”
Section: Epidemiology and Risk Factorsmentioning
confidence: 99%
“…41,42 Similar anatomic problems have been seen with aortoiliac stent grafting for Hawaiian patients of Asian ancestry. 43 In brief, one should keep in mind that performance of thrombectomy without careful consideration of the cause of arterial occlusion may be harmful to patients with atherothrombotic occlusion.…”
Section: Essential Issues For Acute Evt In Asiamentioning
confidence: 99%